1998
DOI: 10.1136/ip.4.4.280
|View full text |Cite
|
Sign up to set email alerts
|

Bicycle helmet promotion among low income preschool children

Abstract: This multifaceted helmet promotion program successfully increased helmet use. Similar home visit protocols may be useful to evaluate the impact of other injury intervention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Legislation has proved highly effective in increasing helmet use,8 and interventions have been identified that significantly improve helmet-wearing 9 10. In the absence of either legislation or intervention, helmet use has been found to be associated with parental encouragement,11 peer influences,11 12 children’s attitudes,13 – 16 and levels of neighborhood deprivation 10 17 18…”
mentioning
confidence: 99%
“…Legislation has proved highly effective in increasing helmet use,8 and interventions have been identified that significantly improve helmet-wearing 9 10. In the absence of either legislation or intervention, helmet use has been found to be associated with parental encouragement,11 peer influences,11 12 children’s attitudes,13 – 16 and levels of neighborhood deprivation 10 17 18…”
mentioning
confidence: 99%
“…10 Programs based outside the medical setting are needed to improve the delivery of injury prevention services to preschool aged children. Previously evaluated interventions have been delivered at preschools, with 11 and without 12 a home based component, and as community education campaigns. 13 14 These services have been provided by public health nurses 15 and by home visitors.…”
mentioning
confidence: 99%
“…Interventions to increase helmet use rates by providing discounted or free helmets coupled with education have shown success. One study increased rates from a 4% baseline to 18% (Parkin et al, 1995), while another increased rates from 43% to 89% (Britt et al, 1998). Programs using community activities, coupons, group purchases, and helmet use reinforcement through rewards and regulations showed success in increasing helmet use rates from a 1% baseline to 33% (Farley et al, 1996).…”
Section: Training and Education Programsmentioning
confidence: 99%